2011
DOI: 10.3113/fai.2011.1164
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hindfoot Ligament Tears and Osteochondral Lesions

Abstract: We believe anatomic studies can be used to clarify the association between traumatic injuries and their sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…2,25,26 This lack of consistency in description may arise from interobserver variability. The difficulties in identifying and defining the components of the medial collateral ligament complex have been described 2,4,11,15,26 and some have concluded that the descriptions are likely the result of artificial divisions of the ligament into separate fascicles during the dissection. 11,32 The spring ligament complex is composed of the superomedial calcaneonavicular and inferior calcaneonavicular ligaments.…”
mentioning
confidence: 99%
“…2,25,26 This lack of consistency in description may arise from interobserver variability. The difficulties in identifying and defining the components of the medial collateral ligament complex have been described 2,4,11,15,26 and some have concluded that the descriptions are likely the result of artificial divisions of the ligament into separate fascicles during the dissection. 11,32 The spring ligament complex is composed of the superomedial calcaneonavicular and inferior calcaneonavicular ligaments.…”
mentioning
confidence: 99%
“…32 The role, presence, and position of the lateral talocalcaneal ligament relative to the CFL are variably reported. 33,34 The close proximity of these two ligaments may cause confusion on imaging following an ankle sprain, where, the lateral talocalcaneal ligament may be mistaken for an intact CFL. 3 The confusion can arise due to variability of the positioning of the lateral talocalcaneal ligament, which is described as either continuous with the CFL, or sitting anterior or posterior to the CFL (See Figure 8).…”
Section: The Cfl Of the Lateral Collateral Ligament Complexmentioning
confidence: 99%